The Implementation of Risk-Based Audit on the Impact of Auditor Competence and Independence on Audit Quality in Bank Perekonomian Rakyat - Suhidayat, Tatang; Fitriana, Fitriana; Agusiady, R. Ricky (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The importance of improving audit quality in Bank Perekonomian Rakyat (BPR) across West Java is evident, given the vital role of auditors in maintaining financial and operational integrity. Auditor competence and auditor independence are two key factors considered to have a significant impact on audit quality, particularly with the adoption of the Risk-Based Audit (RBA) approach. This study aims to analyze the impact of Auditor Competence (KA) and Auditor Independence (IA) on Audit Quality (KAI), both directly and through the Risk-Based Audit (RBA) approach as a mediating variable. The study uses a sample of 99 Internal Audit Executive Officers (PE) from 253 BPRs in West Java. The method employed is a quantitative approach using Partial Least Square (PLS). Data were collected through questionnaires, which were tested for validity and reliability before being analyzed. Hypothesis testing was conducted using the bootstrapping technique to determine the significance of the relationships between variables. The results of the study indicate that both Auditor Competence and Auditor Independence have a significant direct impact on Audit Quality. Auditor Competence and Auditor Independence also have a significant influence on the implementation of Risk-Based Audit. However, the indirect impact of Risk-Based Audit on Audit Quality shows only weak significance, particularly for Auditor Competence. Simultaneous testing also indicates that KA, IA, and RBA together significantly influence KAI, with F-value greater than the F-table. This conclusion suggests that enhancing Auditor Competence and Independence directly is more effective in improving Audit Quality than through the mediation of Risk-Based Audit.